FAKTOR-FAKTOR YANG MEMENGARUHI AKTIFITAS REMAJA DALAM PERILAKU SEKSUAL DI SMP NEGERI 5 BATANG ANGKOLA KECAMATAN BATANG ANGKOLA KABUPATEN TAPANULI SELATAN TAHUN 2020 - Susi Febriani Yusuf; Juliana Lubis (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Sexual behavior in teenagers tends to be increasing. One of the life skills needed to be applied by the teenagers is the skill of how to be assertive. The factors influencing the assertiveness are culture, self-esteem, parents’ parenting pattern, peers, knowledge, self-efficacy, and information media. The purpose of this study was to find out the factors influencing the teenagers’ assertiveness in sexual behavior at SMP (Junior High School) Negeri5BatangAngkola, BatangAngkolaSubdistrict,Tapanuli Selatan District in 2020. The population of this explanatory study was all of the 363 female students of SMP Negeri5 BatangAngkola and 113 female students from grade VIII and grade IX were selected to be the samples for this study through proportional random sampling technique. The data for this study were directly obtained from the female students through questionnaire distribution. The data obtained were analyzed through multiple logistic regression tests at ? = 5%. The result of this study showed that the assertiveness of the female students towards sexual behaviour belonged at the high category (57.5%), and statistically, culture, self-esteem, peers and self-efficacy had influence on the assertiveness towards the sexual behavior in the teenagers at SMP Negeri5 BatangAngkola. The most dominant influencing variable was peer with the regression coefficient value of 5.011. The management of SMP Negeri5 BatangAngkola should increase assertive behavior of their students by including education in the local curriculum in schools and to cooperate with the students’ parents in monitoring tennagers relationship with peers, so that stakeholders teaches teens to be more courageous in making decisions, the respondent must be able to maintain self-esteem.